Coronavirus disease 2019 in patients with neuroendocrine neoplasms: Preliminary results of the INTENSIVE study. (September 2021) - Fazio, Nicola; Gervaso, Lorenzo; Halfdanarson, Thorvardur R.; La Salvia, Anna; Hofland, Johannes; Hernando, Jorge; Sonbol, Mohamad B.; Garcia-Carbonero, Rocio; Capdevila, Jaume; de Herder, Wouter W.; Koumarianou, Anna; Kaltsas, Gregory; et al.
Abstract: Background: Specific data regarding coronavirus disease 2019 (COVID-19) in patients with neuroendocrine neoplasms (NENs) are lacking. The aim of this study is to describe the characteristics of patients with NENs who tested severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) positive. Material and methods: This is a worldwide study collecting cases of patients with NENs along with a positive nasopharyngeal swab reverse transcriptase-polymerase chain reaction (RT-PCR) test for SARS-CoV-2 between June 1, 2020, and March 31, 2021. Centres treating patients with NENs were directly contacted by the principal investigator. Patients with NENs of any primary site, grade and stage were included, excluding small-cell lung carcinoma and mixed adenoneuroendocrine carcinoma. Results: Among 81 centres directly contacted, 88.8% responded and 48.6% of them declined due to lack of cases or interest. On March 31 st, 2021, eight recruiting centres enrolled 89 patients. The median age was 64 years at the time of COVID-19 diagnosis. Most patients had metastatic, non-functioning, low-/intermediate-grade gastroenteropancreatic NENs on treatment with somatostatin analogues and radioligand therapy. Most of them had comorbidities. Only 8% of patients had high-grade NENs and 12% were receiving chemotherapy. Most patients had symptoms or signs of COVID-19, mainly fever and cough. Only 3 patients underwent sub-intensive treatment, whereas most of them received medical therapies, mostly antibiotics. In two third of cases, no changes occurred for the anti-NEN therapy. More than 80% of patients completely recovered without sequelae, whereas 7.8% patients died due to COVID-19. Conclusions: Patients included in this study reflect the typical NEN population regardless of SARS-CoV-2. In most cases, they overcome COVID-19 without need of intensive care, short-term sequelae and discontinuation of systemic oncological therapy. Highlights: Patients with cancer are more susceptible to coronavirus disease 2019. Data regarding patients with neuroendocrine neoplasms and COVID-19 are lacking. This is a worldwide survey specifically focused on patients with COVID-19 and NENs. Most patients with NENs overcame COVID-19 without intensive care and short-term sequelae. Our results provide relevant information to guide healthcare policies in this setting.